2011
DOI: 10.1063/1.3624758
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of polar mesospheric plasma layers: Comparison of theoretical results with observations

Abstract: This paper presents an analytical model for the physical understanding of the charge distribution on ice dust particles in plasma layers of polar mesospheric clouds PMCs (Noctilucent clouds and polar mesospheric summer echoes). For the case of pure ice dust (with high work function), the charging of the particles occurs only because of the accretion of electronic and ionic species on the surface of ice grains. The analysis is based on the number and energy balance of constituents and allows the charge to be on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…5. Approaches used in calculations of e d and N d are described, for example, by Fortov et al (2004), Knappmiller et al (2011), Kopnin et al (2011), andSodha et al (2011).…”
Section: Electron Number Densitymentioning
confidence: 99%
“…5. Approaches used in calculations of e d and N d are described, for example, by Fortov et al (2004), Knappmiller et al (2011), Kopnin et al (2011), andSodha et al (2011).…”
Section: Electron Number Densitymentioning
confidence: 99%
“…Then on the basis of the superposition principle, the entire reflected, transmitted, and absorbed powers are also calculated. Finally, conclusions of the study are given by comparing the calculated results with the experimental results observed by the EISCAT radar [17] .…”
Section: Introductionmentioning
confidence: 97%